2014
DOI: 10.1177/1533317514539540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of APOE and CHRNA7 Genotypes on the Cognitive Response to Cholinesterase Inhibitor Treatment at Different Stages of Alzheimer’s Disease

Abstract: The loss of cholinergic transmission is considered to be an important cause of Alzheimer's disease (AD). Treatment with acetyl cholinesterase inhibitors (ChEIs) shows benefits; however, great heterogeneity has been observed in patient responses. We evaluated apolipoprotein E (APOE) and α7 nicotinic receptor (CHRNA7) single-nucleotide polymorphisms (SNPs) and associated these SNPs with pharmacological responses to ChEIs in a Brazilian population with AD. We studied 177 outpatients using ChEIs, and they were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The CHRNA7 T allele (rs6494223) also associates with a better response to AChEIs and there is further confir mation that APOE4 carriers are the worst responders to conventional AChEIs [51]. Over 70% of AD patients are deficient metabolizers for the CYP2D6/2C19/2C9 trigenic cluster; and for the CYP2D6/2C19/2C9/3A4 tetragenic cluster, more than 80% of the patients exhibit a deficient metabolizer geno phenotype [19].…”
Section: Pathogenic Genesmentioning
confidence: 98%
“…The CHRNA7 T allele (rs6494223) also associates with a better response to AChEIs and there is further confir mation that APOE4 carriers are the worst responders to conventional AChEIs [51]. Over 70% of AD patients are deficient metabolizers for the CYP2D6/2C19/2C9 trigenic cluster; and for the CYP2D6/2C19/2C9/3A4 tetragenic cluster, more than 80% of the patients exhibit a deficient metabolizer geno phenotype [19].…”
Section: Pathogenic Genesmentioning
confidence: 98%
“…Further studies or meta-analyses should consider evaluating the interaction between APOE polymorphism and other genetic variations involving individual differences in drug efficacy or the cholinergic system. In addition to CYP2D6 single nucleotide polymorphism rs1080985, future research can evaluate the interaction with other genetic variations such as the butyrylcholinesterase genotype, phosphatidylinositol-binding clathrin assembly protein (PICALM), paraoxonase 1 gene polymorphism, CHRNA7 genotype, and MAPT genotype [24,26,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 30 studies have investigated the association between APOE genotype and response to cholinergic therapy. The results can be divided into three groups: those showing better response in APOE ɛ4 carriers than in non-carriers [10,11,[23][24][25], those reporting opposite results [5,6,26,27], and those suggesting no impact of APOE genotype on treatment response [2, 7-9, 12-18, 28-43]. The strength of the present findings is that the largest sample sizes and diverse ethnic groups were included, and the pooled data set could provide enough statistical power to evaluate the association between the APOE ɛ4 carrier status and the AChEI treatment response in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although this meta-analysis integrated the results of only a few studies, this finding suggests that there may be an interaction between CYP2D6 and APOE genotypes in modulating the efficacy of AChEIs. The APOE-ε4 allele has been associated with a higher risk of AD, 7 but its potential impact on AChEI response is unclear: some authors found that the response of patients with AD or MD to AChEIs was worse in APOE-ε4 carriers than in non-carriers, 8 but others reported no significant differences. [9][10][11] Overall, these conflicting results and the few studies carried out so far on the topic strengthen the need for further investigation on the roles of CYP2D6 and APOE genotypes and their potential interaction in modulating AChEI effectiveness.…”
Section: Introductionmentioning
confidence: 99%